An mRNA Vaccine Expressing Blood-Stage Malaria Antigens Induces Complete Protection Against Lethal Plasmodium yoelii - Amy C. Ott; Patrick J. Loll; James M. Burns (Vaccines, 2025)
Background and Objectives: To evaluate the mRNA vaccine platform for blood-stage Plasmodium parasites, we completed a proof-of-concept study using the P. yoelii mouse model of malaria and two mRNA-based vaccines. Both encoded PyMSP119 fused to PyMSP8 (PyMSP1/8). One was designed for secretion of the encoded protein (PyMSP1/8-sec); the other encoded membrane-bound antigen (PyMSP1/8-mem). Methods: Secretion of PyMSP1/8-sec and membrane localization of PyMSP1/8-mem were verified in mRNA-transfected cells. As recombinant PyMSP1/8 (rPyMSP1/8) is known to protect mice against lethal P. yoelii 17XL infection, we first compared immunogenicity and efficacy of the PyMSP1/8-sec mRNA vaccine versus the recombinant formulation in outbred mice. Animals were immunized three times followed by challenge with a lethal dose of P. yoelii 17XL-parasitized RBCs (pRBCs). Similar immunization and challenge experiments were conducted to compare PyMSP1/8-sec versus PyMSP1/8-mem mRNA vaccines. Results: Immunogenicity of the PyMSP1/8-sec mRNA vaccine was superior to the recombinant formulation, inducing higher antibody titers against both vaccine components. Following challenge with P. yoelii 17XL pRBCs, all PyMSP1/8-sec-immunized animals survived, with 50% of these showing no detectible pRBCs in circulation (<0.01%). In addition, mean peak parasitemia in PyMSP1/8-sec mRNA-immunized mice was significantly lower than that in the rPyMSP1/8 vaccine group. Both PyMSP1/8-sec and PyMSP1/8-mem were protective against P. yoelii 17XL challenge, with PyMSP1/8-mem immunization providing a significantly higher level of protection than PyMSP1/8-sec immunization considering the number of animals with no detectable pRBCs in circulation and the mean peak parasitemia in animals with detectable parasitemia. Conclusions: mRNA vaccines were highly immunogenic and potently protective against blood-stage malaria, outperforming a similar recombinant-based vaccine. The membrane-bound antigen was more effective at inducing protective antibody responses, highlighting the need to consider antigen localization for mRNA vaccine design.